Do preferential trade agreements favor the liberalization of trade with non-members? The case of the Andean Community - Castillo Thorne, Lakshmi Isabel (Pontificia Universidad Católica del Perú, 2021)
The theoretical literature has not reached a consensus on the effect of PTAs on multilateral liberalization. Empirical studies on this topic have been limited and, like theoretical studies, their results vary. The objective of this study is to find the effect of the Andean Community of Nations on the multilateral liberalization of Peru, by analyzing the variations in the Most Favored Nation (MFN) tariffs applied to non-members as a consequence of the preferential tariff reductions applied by Peru to the members of this PTA. The units of analysis are the tariff lines disaggregated to 6 digits of the Harmonized System for the period 1992-2010. Results show that, for the entire study period, the Andean Community generated a building block. We divided the sample into two sub-periods: 1992-2001 and 2002-2010. For the first period the results show a building block effect; however, for the second half the results changed, and a stumbling block is found. Other variables are also added to observe their effects on changes in external tariffs, such as preferential imports, which, when they present a sizeable preferential margin, cause a reduction in MFN tariffs for the entire sample. Based on these results, we found that the Andean Community did not represent an impediment to multilateral liberalization in Peru.
Keywords: Peru; Andean Community; Preferential Trade Agreements (PTA); https://purl.org/pe-repo/ocde/ford#5.02.01